Pengaruh Program Pengungkapan Sukarela (PPS) Sosialisasi Perpajakan dan Digitalisasi Layanan Pajak Terhadap Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak (KPP) Kota Kediri - Riningsih, Duwi; Eferyn, Krissantina; Yap, Nonni (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The purpose of this research is to determine the influence of the voluntary disclosure program (PPS) on Kediri City Taxpayer compliance, then the influence of socialization of new tax regulations given by tax officers to Taxpayers on Kediri City Taxpayer compliance and finally the influence of use digitalization of tax services as a medium for carrying out tax obligations towards taxpayer compliance in carrying out their tax obligations. The population in this study is all taxpayers registered at the Kediri City Tax Service Office and the number recorded is 110,300 taxpayers consisting of individual taxpayers, corporate taxpayers and treasurer taxpayers. Using SPSS Version 20 data analysis. The results of this test can be concluded that the Voluntary Disclosure Program has a significant effect on taxpayer compliance, Tax Socialization and Tax Service Digitalization do not have a significant effect on taxpayer compliance.